Algebras of Calderón–Zygmund Operators Associated with Para-Accretive Functions on Spaces of Normal Homogeneous Type - Rong Liang; Taotao Zheng; Xiangxing Tao (Mathematics)
In this paper, by using several almost orthogonal estimates and a continuous Calderón reproducing formula associated with para-accretive functions, we obtain the algebras of generalized-product Calderón–Zygmund operators under the condition <semantics>T1(b1)=<msubsup>T1*</msubsup>(b1)=T2(b2)=<msubsup>T2*</msubsup>(b2)=0</semantics>.